(untitled) (Applied Biological Research, 2013)
The present study was conducted to assess the haematinic property of Hygrophila spinosa extract in induced anaemic albino rats with phenylhydrazine. The haematinic activity of orally administered H. spinosa extract (pre-flowering extract @ 40 mg kg-1 body weight) and powdered aerial part (@ 40 mg extract kg-1 body weight) was assessed by treating the induced anaemic rats for 30 days. Treatments ameliorate the anaemic condition by improving haematological parameters and RBC indices. On 30th day post-treatment, the rats treated with plant extract showed more improvement in anaemic condition and increase in body weight in comparison to the rats treated with crude leaf.